Vitreous Inflammatory Cytokines and Chemokines, Not Altered After Preoperative Adjunctive Conbercept Injection, but Associated With Early Postoperative Macular Edema in Patients With Proliferative Diabetic Retinopathy - Sun, Hongyan; Zou, Wenjun; Zhang, Zhengyu; Huang, Darui; Zhao, Jinxiang; Qin, Bing; Xie, Ping; Mugisha, Aime; Liu, Qinghuai; Hu, Zizhong (Frontiers in Physiology, 2022)
Purpose: To investigate the influence of preoperative adjunctive anti-VEGF drug (Conbercept) on vitreous inflammatory cytokines and chemokines profiles and whether those cytokines were associated with early macular edema (ME) after surgery for patients with proliferative diabetic retinopathy (PDR). Methods: In this post hoc analysis of the CONCEPT clinical trial, subjects with PDR underwent vitrectomy were included and vitreous samples were collected at the start of vitrectomy. Levels of vitreous VEGF, 17 inflammatory cytokines, and 11 chemokines were measured using Luminex multiplex technology. Subjects were then divided into groups based on with (Pre-IV) or without (No-Pre-IV) preoperative intravitreous injection of Conbercept; with or without early ME after surgery. Results: There was no difference between Pre-IV (13/30) and No-Pre-IV (7/29) concerning the ratio of patients with early ME (p = 0.17). After preoperative intravitreous injection of Conbercept , VEGF level dramatically decreased (p = 0.001), TNF-α (p = 0.002) and IP-10 (p = 0.018) increased in Pre-IV group. In patients with early ME after surgery, however, a number of cytokines increased, including IL-1β (p = 0.008), IL-2 (p = 0.023), IL-4 (p = 0.030), IL-9 (p =0.02), IL-10 (p = 0.002), IL-12 (p = 0.001), IL-13 (p = 0.031), IL-17A (p = 0.008), TNF-α (p = 0.012), CXCL9 (p = 0.023), G-CSF (p = 0.019), MCP-1 (p = 0.048), and RANTES (p = 0.016). Conclusion: We found the preoperative adjunctive Conbercept injection has limited influence on the levels of vitreous inflammatory cytokines and chemokines in PDR. The elevated levels of a series of cytokines might be associated with early inflammation after vitrectomy, which may lead to postoperative ME.